EVALUASI KINERJA KPU KABUPATEN OGAN KOMERING ULU DALAM SOSIALISASI PEMILIHAN SERENTAK TAHUN 2020 - Feni Yunika (Universitas Bina Taruna Gorontalo, 2022)
The purpose of this study was to analyze the evaluation of the performance of the OKU Regency KPU in socializing and the obstacles faced in the implementation of the simultaneous election socialization in 2020. The method used was descriptive qualitative. Data collection is done by interview. Since the stipulation of the 2020 Simultaneous Elections on September 23, 2020 and the onset of the Covid-19 pandemic, so that the election was postponed to December 9, 2020. Covid-19 as a global pandemic has changed the situation and conditions in the implementation of simultaneous elections. Socialization is an important stage to convey information related to the election. Based on the results of the analysis that has been carried out, the conclusion of this study is that the evaluation of the performance of the OKU Regency KPU in the socialization of the 2020 simultaneous elections was not optimal so that the level of community participation decreased and the existence of Covid-19 health protocol regulations that limited the number of participants and time in socialization became obstacles in the implementation of socialization.